Ultrasound-guided percutaneous needle electrolysis and rehabilitation and reconditioning program following a hamstring injury reduces “return to play” time in professional soccer players: A case series - Jiménez-Rubio, Sergio; Valera-Garrido, Fermín; Minaya-Muñoz, Francisco; Navandar, Archit (Revista Fisioterapia Invasiva / Journal of Invasive Techniques in Physical Therapy, 2020)
This case series follows the treatment protocol after a grade 2 injury to the proximal semitendinosus muscle using US-guided Percutaneous Needle Electrolysis (PNE) and Rehab & Reconditioning program (RRP) in two professional soccer players. The injury was diagnosed using magnetic resonance imaging (MRI) and ultrasound imaging. The players received one session of PNE 48 hours after the injury. The indoor's phase of the RRP started 24 hours after the PNE technique and then the player proceeded to perform an on-field's phase, following which the players returned to train with the team. The effectiveness of the program was measured by comparing the match-performance data collected through Global Positioning System (GPS) in two matches before and five matches after injury and with ultrasound imaging analyzing the evolution of the muscle injury. No adverse effects were identified during or after the US-Guided PNE technique. Both players missed a single competitive game because of injury (layoff= 16 and 14 days). The GPS variables studied showed similar values before and after injury. PNE and PRR protocol improves the results of the initial phase of muscle repair and reduces the time to return to training and return to play, maintaining the GPS parameters that the players need in high performance.
Keywords: hamstring injury; percutaneous needle electrolysis; exercise; professional soccer; return to play